Nash, Jeffery, Et Al., The American People - Creating A Nation And Society - Marran, James (Teaching History: A Journal of Methods, 1997)
With the canons of the revisionists booming across the landscapes of American history, it is especially challenging these days to prepare a textbook that joins the old interpretations with the more recent emphasis on social history without compromising the integrity of the discipline. Written for the college market for the introductory course, this "brief" account provides a fair, balanced, and comprehensive account of how the United States came to be. The authors bring a stylish verve to their writing and provide the reader with anecdotes that are both engaging and memorable. Their purpose is to personalize the American experience by showing how it has been shaped by ordinary as well as extraordinary people.